Synthesis, characterization and biological applications of some acetylpyridine, acetophenone derivatives and their metal complexes / Nura Suleiman Gwaram - Suleiman Gwaram, Nura (2014)

(untitled)
A series of compounds derived from 2-acetylpyridne or acetophenones with morpholine, piperazine and piperidine moeity were synthesized and structurally characterized. The compounds were analysed for in silico, in vitro and in vivo biological applications (anti-cancer, anti-bacteria, anti-Alzheimer and anti-ulcer). They were first screened for in vitro anti-bacterial activity against Methicillin-resistant Staphylococcus aureus (MRSA), Acinetobacter baumanni (AC), Klebsiella pneumonie (KB) and Pseudomonas aeruginosa (PA) using the disc diffusion and micro broth dilution assays. Based on the overall results, they showed the highest activities against MRSA while a weak antibacterial activity was observed against A. baumanii and P. Aeruginosa. Another second series of 2-acetypyridine and acetophenone derivatives of gallic hydrazide-derivatives were synthesized and examined for their antioxidant activities and in vitro and in silico acetylcholinesterase inhibition. The ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays revealed that all the compounds have strong antioxidant activities. Molecular docking simulation of the ligand-enzyme suggested that they positioned in the enzyme’s (acetylcholinesterase) active-site gorge. This work warrants further preclinical studies to assess the potential for these novel compounds for the treatment of Alzheimer Disease. Furthermore, some copper(II) and zinc(II) complexes were investigated for in vivo gastroprotective effects against ethanol-induced superficial hemorrhagic mucosal lesions in rats. Rats were divided into 7 groups. Groups 1 and 2 were orally administered with Tween 20 (10% v/v). Group 3 was orally administered with 20 mg/kg omeprazole/cimetidine (10% Tween 20). Groups 4–7 received 10, 20, 40, and 80 mg/kg of the complex (10% Tween 20), respectively. Tween 20 (10% v/v) was given orally to group v 1 and absolute ethanol was given orally to groups 2–7, respectively. Rats were sacrificed after 1 h. Group 2 exhibited severe superficial hemorrhagic mucosal lesions. This study describes a model to produce extensive gastric necrosis in rats by induction with absolute ethanol. The administration of complexes at 1hour before induction with absolute ethanol reduced or totally eliminated lesions.